The Velislav Bible, the finest picture Bible of the late Middle Ages
1 online resource.
Keywords: The Velislav Bible is one of the most beautiful medieval Bohemian manuscripts. It is a heavily illustrated manuscript that contains only short selections of the text, that instruct the reader about the story depicted. The last picture in the manuscript shows a man kneeling before St. Catherine, identified as Velislav, hence the name of the manuscript. The Bible comprises stories from the Books of Genesis and Exodus, visions of Daniel, and the stories of Samson as well as of Judith. The narrative of the Antichrist precedes the Christological part. The New Testament continues with the Book of Revelation, stories following the Ascension of Christ, and key events from the lives of St. Peter and St. Paul. The manuscript closes with the legend of St. Wenceslas, the patron saint of Bohemia. The essays in The Velislav Bible, Finest Picture-Bible of the Late Middle Ages: Biblia depicta as Devotional, Mnemonic and Study Tool analyze the manuscript from historical, textual, art-historical, and iconographic perspectives. However, a shared concern of all the authors is to think about its functions. An edition of the Latin titulis is being published here for the first time.